Implementasi Penilaian Daur Hidup Produk Susu Sapi Segar (Studi Kasus Koperasi Peternak MJM) - Bunga Cahyaputri; Mohamad Yani; Sugiarto Sugiarto (Jurnal Teknologi Industri Pertanian, 2021)
The growth of the milk industry in Indonesia is increasing every year. This is due to population growth, Indonesian income increasing, and their awareness of consuming milk benefit. Milk production in Indonesia comes from small and medium-term farmers, requiring Koperasi to improve the quality of dairy products in Indonesia. Koperasi Mitra Jaya Mandiri (MJM) consists of dozens of small local farm which all activities are still done manually. Activities of Koperasi MJM, farmers and milk transportation have an impact on the environment. The objective of this research is identify inputs, outputs and environmental impacts in the production of 1 kg of fresh milk (case study of Koperasi MJM). The methods used are life cycle assessment (LCA) with three impact categories: global warming (GWP), eutrophication potential (EP) and acidification potential (AP). The boundary of LCA study is "cradle to gate", which include: feed production, dairy farming activities, transportation of milk to Koperasi, cooling of milk in Koperasi and transportation of milk to factory. Based on LCA results, the environmental impact of GWP, EP and AP 1 kg of Koperasi MJM fresh milk equals 3.45 kg CO2 eq, 0.018 kg PO43- and 0.0208 kg SO2 eq. The stage of dairy farming activities has the highest environmental impact in these three categories. Environmental impact reduction can be done by processing feces of cow, or choosing feed additive that more environmentally friendly. Key words: Life Cycle Assessment, fresh milk, cradle to gate, environmental impact, diary farm